An overview of translational research in bone graft biomaterials. Issue 4 (4th March 2023) - Kumawat, Vijay Shankar; Bandyopadhyay-Ghosh, Sanchita; Ghosh, Subrata Bandhu
Abstract: Natural bone healing is often inadequate to treat fractures with critical size bone defects and massive bone loss. Immediate surgical interventions through bone grafts have been found to be essential on such occasions. Naturally harvested bone grafts, although are the preferred choice of the surgeons; they suffer from serious clinical limitations, including disease transmission, donor site morbidity, limited supply of graft etc. Synthetic bone grafts, on the other hand, offer a more clinically appealing approach to decode the pathways of bone repair through use of tissue engineered biomaterials. This article critically retrospects the translational research on various engineered biomaterials towards bringing transformative changes in orthopaedic healthcare. The first section of the article discusses about composition and ultrastructure of bone along with the global perspectives on statistical escalation of bone fracture surgeries requiring use of bone grafts. The next section reviews the types, benefits and challenges of various natural and synthetic bone grafts. An overview of clinically relevant biomaterials from traditionally used metallic, bioceramic, and biopolymeric biomaterials to new generation composites have been summarised. Finally, this narrative review concludes with the discussion on the emerging trends and future perspectives of the promising bone grafts.